2012
DOI: 10.3892/or.2012.2151
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces MMP-9 and cell migration via the p38 kinase and PI-3K pathways in HT1080 human fibrosarcoma cells

Abstract: Abstract. 4', is a grape polyphenol present in various plants, food products, red wine and grapes. Resveratrol has anti-inflammatory, anticarcinogenic, anti-oxidant and anti-aging properties. Matrix metalloproteinases (MMPs) are key enzymes involved in the degradation of the extracellular matrix, and their expression may be regulated in cancer metastasis. In the present study, we aimed to evaluate the effect of resveratrol on MMPs and cell migration, and to understand the mechanism of action in HT1080 human fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…One of the first steps of metastasis is the degradation of the basement membrane and stromal extracellular matrix (ECM), which form physical barriers to restrict cell movement [5,6]. During this process, matrix metalloproteinases (MMPs) are involved in the breakdown of the ECM components, thereby facilitating tumor progression and metastasis [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the first steps of metastasis is the degradation of the basement membrane and stromal extracellular matrix (ECM), which form physical barriers to restrict cell movement [5,6]. During this process, matrix metalloproteinases (MMPs) are involved in the breakdown of the ECM components, thereby facilitating tumor progression and metastasis [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…83 Contrary to this, Gweon and Kim showed that treatment of HT1080 human fibrosarcoma cells with resveratrol 50 mM results in inhibition of p38 phosphorylation resulting in increased MMP-9 secretion. 42 One of the in vivo studies using streptozotocin-induced diabetic rats showed that resveratrol favorably shifts ERK1/2 and p38 MAPK activation. 84 In contrast to all the above observations, Jiao et al showed that treatment of glioblastoma-initiating cells with resveratrol although reduced Akt and mTOR phosphorylation, did not affect the phosphorylation of the ERK1/2, p38, and JNK pathways.…”
Section: Resveratrol Affects Activation Of Transcription Factorsmentioning
confidence: 99%
“…82 Contrary to the above finding, Gweon and Kim showed that treatment of HT1080 human fibrosarcoma cells with resveratrol (50 mM) for 24 h causes increased MMP-9 secretion due to inhibition of Akt phosphorylation. 42 Mitogen activated protein (MAP) kinase pathway. The MAP kinases are involved in the regulation of MMPs and are modulated by transcription factors.…”
Section: Resveratrol Affects Activation Of Transcription Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, at uncontrolled levels, ROS can cause a wide variety of human disorders and diseases, including cancers [11,12]. Several studies indicate that antioxidants exhibit anti-invasive activity against cancer cells by inhibiting MMP expression [13,14].…”
Section: Introductionmentioning
confidence: 99%